The Benefits of Fishbean Biscuits as a Local Supplement Rich in Animal Protein for Malnourished and Stunted Toddlers in Central Bengkulu Regency - Emy Yuliantini (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2026)
Bckground: Stunting and malnutrition among toddlers are major public health challenges, particularly in Indonesia. One effort is the development of supplementary feeding (PMT) based on local foods, such as fish and peanut biscuits. This study aims to determine the effect of fish and peanut biscuits on toddlers' nutritional status, hemoglobin (HB) levels, and the safety of kidney function as measured by urinary protein. Method: This study used a pre-experimental one-group pre-test post-test design involving 30 children aged 6–60 months. The intervention consisted of providing Fishbean biscuits at 50 grams/day for 40 days along with booklet-based nutrition education. Data collected included anthropometric measurements, hemoglobin levels, and dietary intake, which were analyzed using univariate and bivariate methods with the Independent Sample t-test. Result: Providing Fishbean biscuits increased energy, protein, and fat intake, but had no effect on carbohydrate intake. This intervention effectively increased weight-for-age (BW/A), but did not show a significant effect on height (H/A), BW/H ratio, or hemoglobin levels. Furthermore, the absence of changes in urinary protein indicates that consuming Fishbean biscuits is safe for toddlers' kidney function. Conclusion: Fish nut biscuits can be integrated into the PMT program. Exploring the long-term impact of fish nut biscuits on the nutritional status of toddlers is recommended.